Essays on fiscal sociolology/ edited by Jurgen G.Backhaus - "Backhaus, Jurgen G.(ed.)" (Germany, 2005)
Due to the widespread dissatisfaction with the way fiscal sociology is being neglected while benefiting by its ever-growing importance, the volume Essays on Fiscal Sociology aims to provide a source, reference, and teaching supplement for the field of fiscal sociology. The essays comprised in this book were originally prepared for and read at the Erfurt Conferences on Fiscal Sociology. Please note that this conference is open to all researchers in this field internationally and it is taking place in the second week of October, before the semester starts.
Keywords: Sociology